KEBIJAKAN DAERAH DALAM PROGRAM PENGENTASAN KEMISKINAN DALAM RANGKA PENINGKATAN KESEJAHTERAAN RAKYAT BERDASARKAN UNDANG UNDANG NO 13 TAHUN 2011 DI KABUPATEN DEMAK - Sri Kusriyah; Dina Aulia (UNISSULA, 2015)
Efforts to prosper the poor to this day is still partial scattered in various provisions of legislation, so it is necessary a law that specifically regulate the poor. This research is a descriptive empirical research specifications of the data collection techniques that are exposure, aims To obtain a complete picture of the legal situation prevailing in a particular place. A descriptive study is intended to provide as much data as possible about humans, circumstances or other symptoms. Data analysis techniques using quantitative data analysis methods.Based on the results of research and analysis that has been done can be concluded that the strategic policy of the region in poverty alleviation programs based on Law No. 13 of 2011 on Fakir Poor in Demak District is still very minimal because new in 2013 is being discussed on the Draft of Regional Regulation on Poverty Reduction, Obstacles faced in the implementation of poverty alleviation programs based on Law No. 13 of 2011 on the Poor in Demak Regency is the lack of regulations that support poverty alleviation and the lack of budget APBD..